Pengaruh Budaya Organisasi Terhadap Etika Profesi Akuntan - Michael (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2025)
This study aims to examine and analyze the influence of organizational culture on the professional ethics of accountants. Using a quantitative approach with a survey method, this research collected data from accountants working in the private sector in the Jakarta area. A total of 120 respondents participated in this study, with data collected through a questionnaire whose validity and reliability had been tested. Data analysis was performed using descriptive statistics and multiple linear regression. The results show that organizational culture has a significant and positive influence on the professional ethics of accountants. This finding is supported by a regression analysis which found that dimensions of organizational culture, particularly ethical leadership and the reward system, are strong predictors of accountants' ethical behavior. Additional qualitative interviews confirmed that while a formal code of ethics exists, its implementation is highly dependent on a supportive culture and consistent enforcement. Thus, this study concludes that to strengthen the professional ethics of accountants, companies must focus on developing and maintaining a healthy organizational culture. The practical implications are the need for investment in developing leadership with integrity and designing a balanced incentive system to maintain the integrity of the accounting profession.